The Embodiment of Intangible Investment Goods : A Q-Theory Approach - Belhocine, Nazim (IMF Working Papers; Working Paper ;, 2010)
This paper extends the q-theory of investment to model explicitly the decision of firms to invest in intangibles and measures the contribution of intangible goods to the overall capital stock in the U.S. The model highlights the embodiment of intangible goods in tangibles and the role of relative price movements in the measurement of the contribution of each type of investment to the overall capital stock. The downward trend in the aggregate investment deflator series reported by national accounts is found to have a significant downward bias in the 90s. The model also shows that the growth in the overall capital stock from the late-80s until 2000 was driven mainly by an increase in the contribution of intangibles. However, the contribution of intangibles fell consistently after 2000. These results underscore the importance of accounting for the movements in the price of intangibles rather than focusing only on their rising share in overall investment.